2004
DOI: 10.1071/ah040285
|View full text |Cite
|
Sign up to set email alerts
|

After-hours general practice clinics are unlikely to reduce low acuity patient attendances to metropolitan Perth emergency departments

Abstract: Objective: To model the effectiveness of afterhours general practice (GP) in reducing metropolitan Perth emergency departments' (ED) low acuity patient (LAP) attendances and costs. Methods:We estimated LAP attendances by comparison of the product of (A) the difference between self-referred and GP-referred ED discharge rates and (B) total self-referred attendances (LAP attendances = A B). We then compared after-hours ED LAP attendance rates and costs with inner metropolitan "working-week" ED LAP attendance rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 8 publications
1
26
0
1
Order By: Relevance
“…The average cost would, therefore, decrease as the number of patients increases 38. This variability in the magnitude of any cost saving is consistent with findings in the North American and Australian literature, with the suggestion that the true costs of non-urgent care in the ED are relatively low 39 40…”
Section: Discussionsupporting
confidence: 81%
“…The average cost would, therefore, decrease as the number of patients increases 38. This variability in the magnitude of any cost saving is consistent with findings in the North American and Australian literature, with the suggestion that the true costs of non-urgent care in the ED are relatively low 39 40…”
Section: Discussionsupporting
confidence: 81%
“…Several models were discussed at length, including the provision of low acuity after-hours service through a general practice in Maryborough. However, a study by Nagree et al, 1 found that while low-acuity patients are a constant but inexpensive ED workload, diverting them to a general practice lowacuity service is unlikely to significantly reduce the ED attendances and costs. The consensus decision by the GPs present was to assist by working in the EDs of both HBH and MBH, in addition to the internal medicine ward at MBH.…”
Section: Sequence Of Eventsmentioning
confidence: 99%
“…[15][16][17][18] They further emphasise that urgency Category 4 and 5 patients do not equate to primary care patients. If, despite definitional issues, strategies are to be developed to influence patients in this group into altering their pattern of accessing health care, then a broad set of factors must be considered.…”
Section: Importancementioning
confidence: 99%